2014
DOI: 10.1007/s40362-014-0027-x
|View full text |Cite
|
Sign up to set email alerts
|

A Question of Attire: Dressing Up Bacteriophage Therapy for the Battle Against Antibiotic-Resistant Intracellular Bacteria

Abstract: More and more bacteria are developing severe antibiotic resistance. Among them are important intracellular pathogens such as Mycobacterium tuberculosis. Alternatives to classical antibiotics are urgently needed and bacteriophage therapy is a promising candidate for alternative or supplemental treatment. Until now, bacteriophages have been thought to be non-suitable for therapy against intracellular pathogens. Still, a few studies have been carried out to assess the efficacy of bacteriophage therapy against int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Phages may also gain entry into the body via eukaryotic cell uptake through a number of proposed routes. Phages have been documented to enter eukaryotic cells through a Trojan Horse mechanism, whereby phages infect or integrate into a bacterial host, which is in turn engulf by, or enters a eukaryotic cell and subsequently releases the phage particles . Numerous studies have also reported targeted gene delivery to eukaryotic cells utilizing phage‐display mechanisms, whereby phages are engineered to display peptides complementary to cell‐surface integrins that trigger receptor‐mediated endocytosis .…”
Section: Across the Cell Layermentioning
confidence: 99%
See 2 more Smart Citations
“…Phages may also gain entry into the body via eukaryotic cell uptake through a number of proposed routes. Phages have been documented to enter eukaryotic cells through a Trojan Horse mechanism, whereby phages infect or integrate into a bacterial host, which is in turn engulf by, or enters a eukaryotic cell and subsequently releases the phage particles . Numerous studies have also reported targeted gene delivery to eukaryotic cells utilizing phage‐display mechanisms, whereby phages are engineered to display peptides complementary to cell‐surface integrins that trigger receptor‐mediated endocytosis .…”
Section: Across the Cell Layermentioning
confidence: 99%
“…Similar studies have shown evidence of filamentous phage and Myoviridae within mammalian cells, although these phages were either engineered to display exogenous protein markers or the mechanism of cellular entry was not clearly delineated . Several review articles have broached the topic of phage‐epithelial transcytosis, but few attempts have been made to experimentally validate whether phage transcytosis occurs naturally and via which route . Thus, the primary mechanism that native phages use to access the eukaryotic cell remains unknown.…”
Section: Across the Cell Layermentioning
confidence: 99%
See 1 more Smart Citation
“…There is some debate as to whether bacteriophages would be able to diffuse across eukaryotic cell membranes killing intracellular bacteria infecting macrophages and other eukaryotic cells. Some recent in vitro studies have shown free phage entry into macrophages and other non-phagocytic eukaryotic cells however, the mechanisms of entry remain unclear (Nieth et al, 2015b ; Zhang et al, 2017 ). Intracellular phage entry into eukaryotic cells has been explained to occur either through phagocytosis of phage infected bacteria or via bacterial induced endocytosis (Finlay, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that non-virulent Mycobacterium smegmatis and Mycobacterium avium transiently infected with the lytic phage TM4 were able to deliver the phage into Mycobacterium tuberculosis infected macrophages in a “Trojan Horse” approach (Broxmeyer et al, 2002 ). In a similar manner, liposome encapsulated phages may permit phage access to intracellular pathogens for the treatment of serious infections, such as those caused by M. tuberculosis, S. aureus , and E. coli (Nieth et al, 2015b ).…”
Section: Introductionmentioning
confidence: 99%